Assessing the Factors that Influence Entrepreneurship in Nigeria - Abubakar, S. Garba; Shazali, Abu Mansor; Fariastuti, Djafar (Publishingindia.com, 2013)
The purpose of the paper is to examine factors influencing entrepreneurship both at individual and aggregate level. The approach for data collection has been broken down in two in order to address the differences in using different levels of analysis. At the individual level, survey has been used to collect data. Ordinary lease square method was employed in estimating the coefficients of the variables in the model. While at the aggregate level, time series data were collected from various official sources. Vector autoregressive (VAR) framework was adopted to systematically capture the rich dynamic in multiple time series. Start-up capital and gender were found to be statistically significant in influencing entrepreneurship at individual level. It is also evident that most of the entrepreneurs are driven by opportunity to start up business. The result at the aggregate level shows that there is long run relationship among the variables. The positive influence of unemployment on entrepreneurship is an indication of the presence of necessity entrepreneurship. Poverty and economic growth influenced entrepreneurship negatively. Therefore, the paper reveals the presence of both necessity and opportunity entrepreneurship in the country. There is paucity of studies on this area that integrate individual and aggregate level. Therefore, the paper attempts to fill this research gap and to provide holistic information on entrepreneurship in Nigeria context.